Burnout Syndrome Assessment Scale in University Students: construction and validity evidence - Carlotto, Mary Sandra (2020)
Burnout syndrome (SB) in students consists of a negative response to chronic stress related to the roles and activities of the academic context. The objective of the present study was to present the development and validity evidences of a new SB assessment tool among Brazilian university students. The final version was applied to 1,169 university students, who also answered a questionnaire of sociodemographic and academic data and the Perceived Stress Scale (PPS-10). The sample was divided in half, randomly, to carry out the factorial analyzes. Exploratory factorial analysis and parallel analysis indicated a three-dimensional structure. Confirmatory factorial analysis showed that the three-factor structure is fairly well fitted to the data, either in the first or second order. The reliability of the general scale and its dimensions was satisfactory in both estimators: Cronbach’s alpha and McDonald’s omega. The overall scale, as well as its dimensions, showed a significant positive correlation as well as good indexes of sensitivity and specificity in relation to PPS-10, used as gold standard. The study contributes with an instrument of SB evaluation among university students, built from the reality of this population.